Osteuropa - Wachstumsmarkt für Low Cost Airlines. - Bjelicic, Borislav (Deutscher Verkehrs-Verl., 2004)
Kein Thema beschäftigt die Luftverkehrsbranche weltweit derzeit mehr als das Thema Low Cost Airlines. Jetzt expandieren diese neuen Anbieter auch verstärkt nach Osteuropa. Ein neuer Entwicklungsschub geht hierbei von den Beitrittskandidaten aus, die im Mai 2004 zur Europäischen Union gestoßen sind. difu

The aviation industry is currently in a process of profound change. One reason for this is the low-cast phenomenon. Any low-cost airlines have been started n the last two years in Northwest Europe. Airline deregulation in the European Union was one of the causes for the success of the low-cost model. With the enlargement of the European Union and the growing economic integration between the European North and South, there will be more growth potential for he low-cost carriers. The presence of an increasing number of low-cost carriers has a significant impact on the profitability of the traditional flag carriers as well as the traditional charter airlines. Also the cross border railway traffic will be seriously affected. These carriers have to adapt to the new competitive situation. The only winner, who is al ready known, is the consumer. difu
Keywords: Verkehr; Luftverkehr; Verkehrsinfrastruktur; Flughafen; Flugzeug; Billigflug; Fluggesellschaft; Luftverkehrsunternehmen; Verkehrsmarkt; Expansion; Reiseziel; EU-Beitrittsland; Passagieraufkommen; Fluggast